EFFECT OF HEAT MOISTURE TREATMENT OF SAGO STARCH ON ITS NOODLE QUALITY - Purwani, E .Y.; ., Widaningrum; Thahir, R .; ., Muslich (Indonesian Journal of Agricultural Science, 2006)
Sago starch has potential as source of flour for noodle. However, noodle made of sago starch has only been limitedly utilized due to the absence of gluten and lack of desired functional properties. Heat moisture treatment (HMT) is a promising technique for improving quality of sago noodle. The objectives of the present work were to study the effect of HMTof sago starch on its noodle quality. Four different origins of sago starch, i.e. Tuni, Ihur, Molat, and Pancasan, were treated with HMT method. HMT was performed by exposing the starch to high temperature (110oC for 16 hours) at moisture content of 25%. Sago starch was then processed into noodle. It was prepared by mixing the sago starch with binder (completelygelatinized starch and additive) into dough. The dough was pressed manually through a container with holes in the base. Noodles strains were steamed for 2 minutes and dried at 50oC in a convection drier. As the control, non-HMT sago starch was used and evaluated. Parameters evaluated were starch properties, physical strength, and cooking and sensory quality of the noodles. Analyses of variance was subjected to allparameters. Research results showed that the starch exposed to HMT changed its pasting profile from initial type A before treated to type B after treated. The noodle quality was also improved. Noodles resulted from starch treated with HMT showed higher firmness and elasticity, but they have lower stickiness compared to those of non-HMT. Less cooking lossand rehydration weight were also found, however, HMT increased cooking time of the noodles. HMT on Pancasan sago starch resulted in noodles which were preferred most by panelists. However, consumer testing is recommended to further validate consumers preferences to the sago starch noodles. The study indicated that sago starch could be potentiallyused as raw material for noodles to increase the consumption of sago-based food.